2020
DOI: 10.1111/jgs.16477
|View full text |Cite
|
Sign up to set email alerts
|

American Geriatrics Society Policy Brief: COVID‐19 and Nursing Homes

Abstract: This policy brief sets forth the American Geriatrics Society's (AGS's) recommendations to guide federal, state, and local governments when making decisions about care for patients with coronavirus disease 2019 (COVID‐19) in nursing homes (NHs) and other long‐term care facilities (LTCFs). The AGS continues to review guidance set forth in peer‐reviewed articles and editorials, as well as ongoing and updated guidance from the Centers for Medicare and Medicaid Services, the Centers for Disease Control and Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 3 publications
1
58
0
8
Order By: Relevance
“…This could explain, in part, the older age of infected patients in our study when compared to those of other regions. Individuals living in residential care homes are amongst the most susceptible to poorer health outcomes from COVID-19, mainly due to the higher number of underlying chronic conditions, immunosenescence, and the potential for rapid transmissibility from asymptomatic and pre-symptomatic patients [20][21][22]. Although the infection was more prevalent in women, we found that COVID-19 mortality was more common in men.…”
Section: Discussionmentioning
confidence: 62%
“…This could explain, in part, the older age of infected patients in our study when compared to those of other regions. Individuals living in residential care homes are amongst the most susceptible to poorer health outcomes from COVID-19, mainly due to the higher number of underlying chronic conditions, immunosenescence, and the potential for rapid transmissibility from asymptomatic and pre-symptomatic patients [20][21][22]. Although the infection was more prevalent in women, we found that COVID-19 mortality was more common in men.…”
Section: Discussionmentioning
confidence: 62%
“…Residents of aged care facilities are a vulnerable population because of older age and multimorbidity. 12 Disease severity and mortality due to COVID-19 has been shown to be higher among people with these characteristics. 13 Strategies to ensure access to essential medications, including end-of-life medications, are important.…”
Section: Medication Imprest Systems In Residential Aged Carementioning
confidence: 99%
“…In addition, a further 66 cases of COVID-19 in 50 staff members (incidence rate, 29%) and 16 visitors were traced to this facility. 5,6 Health authorities 7,8 and geriatric societies [9][10][11] have published guidelines for long-term care facilities and nursing homes to prevent and control infection.…”
Section: Introductionmentioning
confidence: 99%